TINJAUAN STRUKTUR ATAS GEDUNG INSTALASI BEDAH SENTRAL RSUD KOTA PADANG PANJANG - Fadhila, Raul; Bastian, Elfiani; Putra, Yorizal (Ensiklopedia Research and Community Service Review, 2024)
In planning the superstructure of central surgical installation RSUD house in the city of Padang Panjang, This building is used as a place to accommodate patients, rooms for doctors and nurses and a place to perform surgical operations. In the formulation of the problem for the construction of this RSUD, the researcher only draws details according to the calculation of the dimensions of the columns, beams, plate thickness and reinforcement design. The method used is preliminary design, loading and modeling as well as structural analysis calculations. From the planning results, the main beam dimensions are 35 cm x 70 cm using lots of 7D16 reinforcement, B2 beam 25 cm x 40 cm lots of 4D19 reinforcement. Columns on the 1st ,2nd floor dimensions used 45 cm x 45 cm with lots of 12D19 bone. The floor slabs use plain steel reinforcement Ø10 - 150 mm for the top bottom with a floor plate thickness of 12 cm. The conclusion is to plan a building should be preceded by a feasibility study so that when carrying out structural calculations later can obtain satisfactory planning results both in terms of quality, cost and time. Keywords: SNI 2019, Structural Analysis, Earthquake Spectrum Response, Loading